Towards developing scalable climate-smart village models: approach and lessons learnt from pilot research in West Africa - Bayala, Jules; Zougmoré, Robert B.; Ky-Dembélé, Catherine; Bationo, B. André; Buah, Saaka S.J.; Sanogo, Diaminatou; Somda, Jacques; Tougiani, Abasse; Traoré, Kadari; Kalinganire, Antoine (World Agroforestry Centre, 2016)
This occasional paper presents a report from a project on “Developing community-based climate smart agriculture through participatory action research in CCAFS benchmark sites in West Africa” which is a joint initiative of CCAFS-West Africa programme and ICRAF-WCA. Other key players of the project are the national research institutes namely Institut de l’Environnement et de Recherches Agricoles (INERA, Burkina Faso), Savanna Agriculture Research Institute of the Council for Scienti c and Industrial Research (CSIR-SARI, Ghana), Institut d’Economie Rurale (IER, Mali), Institut Senegalais de Recherche Agricole (ISRA) and Institut National de Recherche Agronomique du Niger (INRAN). After three years of implementation, the present document is describing the approach used and the lessons learnt. The project used participatory action research approach to test combinations of innovations to address the triple goal of climate smart agriculture which are adaptation to climate change, mitigation of the effects of climate change and attaining food security.